Resistorless realization of current-mode first-order allpass filter using current differencing transconductance amplifiers - Tangsrirat, Worapong; Pukkalanun, Tattaya; Surakampontorn, Wanlop (My University, 2010)
This paper presents a realization of a current-mode first-order allpass filter using two current differencing transconductance amplifiers (CDTAs) as the active components and one virtually grounded capacitor as the only passive component. The proposed filer requires no external resistor and is electronically adjustable by varying the external bias current of the CDTA. No component-matching constraints are required. The circuit realizes both inverting and non-inverting types of allpass filters, and also exhibits high-output impedances, which are easy cascading in the current-mode operation. As an application of the proposed CDTA-based allpass section, a current-mode quadrature oscillator is realized. PSPICE simulation results are given to confirm the theoretical analysis. © 2010 Elsevier Ltd. All rights reserved.
Keywords: Allpass filter; Current differencing transconductance amplifier (CDTA); Current-mode circuits